2018
DOI: 10.5578/tt.66535
|View full text |Cite
|
Sign up to set email alerts
|

Obez olan ve olmayan OSAS’lı olgularda nötrofil lenfosit oranının önemi var mı?

Abstract: SuMMArYDoes the neutrophil-to-lymphocyte ratio have any importance between subjects with obstructive sleep apnea syndrome with obesity and without obesity? Introduction: An increase in the incidence of OSAS (obstructive sleep apnoea syndrome) has been seen due to the reported association between OSAS and obesity. Subjects are predisposed to cardiovascular disease due to systemic inflammation caused by the interactions between obesity and OSA. Inflammatory markers could be used to predict the degree of systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The higher values of leucocytes and especially higher N/L ratio, which is a biomarker of subclinical inflammatory response 46 , 47 , supports the suspicion that these dogs had at least a hepatic parenchyma inflammation. Likewise, humans affected by OSA also demonstrate higher N/L ratio, positively correlated to the OSA severity 48 and mitigated by continuous positive airway pressure (CPAP) therapy 48 , 49 .…”
Section: Discussionmentioning
confidence: 63%
“…The higher values of leucocytes and especially higher N/L ratio, which is a biomarker of subclinical inflammatory response 46 , 47 , supports the suspicion that these dogs had at least a hepatic parenchyma inflammation. Likewise, humans affected by OSA also demonstrate higher N/L ratio, positively correlated to the OSA severity 48 and mitigated by continuous positive airway pressure (CPAP) therapy 48 , 49 .…”
Section: Discussionmentioning
confidence: 63%
“…Previous research showed that an elevated NLR is associated with the increased concentration of various proinflammatory cytokines [51,52] that may cause cellular DNA damage. However, although research studied the relationship between this parameter and various chronic diseases with inflammation [53][54][55][56][57], there are few papers on its relationship with obesity and the quality of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies emphasize the role of NLR as a potential inflammation marker in not only cardiac and non-cardiac disorders, but also autoimmune conditions and infections (44, 45). Inflammatory status is reflected by neutrophil counts, while the lymphocyte count is linked to the nutritional status and general stress (46). The increase in neutrophil count was proven to be directly related to the degree of obesity (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the fact that in our study we did not find a significant increase in neutrophil count among the study group might be explained by the young age of our subjects, resulting in an insufficient amount of time for chronic inflammation to occur. Moreover, multiple studies have focused on assessing the role of NLR and PLR in patients with related-comorbidities; a study performed with 155 obese and non-obese patients with obstructive sleep apnea found significantly higher values in terms of NLR among obese individuals (46). Metabolic syndrome related obesity is another disorder commonly associated with chronic inflammation that was found to be related with NLR (48).…”
Section: Discussionmentioning
confidence: 99%